Planning Information Technology–Knowledge Worker Systems - Gaimon, Cheryl (Management Science, 1997)
A model is introduced to examine the long-term planning associated with the purchase and implementation of information technologies (IT) that indirectly contribute to output through enhancement of an organization's knowledge workers. For example, architectural firms in the service industry and manufacturers developing new or modified products invest in computer-aided design systems (CAD) to increase the volume of output generated by the engineering specialist. A critical element of the IT-knowledge worker model introduced is the inclusion of implementation-related dynamics. In particular we model both the short-term disruption to output that typically occurs at the start of the implementation period and the effect of worker learning during implementation. The ability of the organization to generate output is examined in relation to the levels of workforce, information technology, worker skill, and a variety of features of the IT. Seven production function attributes are introduced to quantify the manner in which output is generated for the IT-knowledge worker system. The production function is embedded into an optimization model in which profit is maximized. The formulation is dynamic in order to capture important elements of the decision-making environment, including the learning process, technological change, increasing wages, and changes in the labor supply. Optimal policies are obtained depicting the manner in which an organization should hire and fire its workforce and acquire information technology over time. A fundamental result is obtained establishing the existence of a complementary relationship between IT and knowledge workers. It is shown that a greater level of effective IT increases the desirability of hiring additional workers. In addition, as the ability of the IT to enhance knowledge worker productivity improves (reflecting IT features such as ease of use, functionality, connectivity, etc.), the desirability of hiring additional workers increases. Similarly, due to a high volume of workforce or a high level of worker skill, the desirability of acquiring IT increases. It is also shown that if an organization ignores the nature of the lagged effect of workforce learning, or if the impact of workforce learning on output is underestimated, then the projected volume of output over time is largely exaggerated. These results have important implications to management decision making with respect to effective implementation practices, technology choice issues, and workforce selection. Numerical results are generated to explore the effect of organizational size. It is shown that a smaller organization (as measured by the size of its workforce) relies more heavily on information technology to enhance worker productivity and generate output. Lastly, in response to higher wages, analytic results are derived demonstrating that an organization should reduce its level of hiring and its purchase of IT. Furthermore, numerical results show that an organization paying higher wages should allocate a greater amount of IT per worker to enhance productivity.